Dolutegravir Loaded Solid Self-Micro-Emulsifying Drug Delivery System for Enhanced Solubility and Dissolution (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Dolutegravir sodium (DG) is a recently approved antiretroviral drug belonging to BCS class II having poor aqueous solubility and only 16% oral bioavailability. Hence aim of the present work was to develop solid self micro-emulsifying drug delivery system (S-SMEDDS) of Dolutegravir for enhanced solubility and dissolution behaviour. Initially, solubility of DG was checked to select oil, surfactant, and co-surfactant. Pseudo ternary phase diagram was constructed to identify microemulsion region. Liquid SMEDDS of DG were prepared using Campul MCM, Tween 80 and Transcutol P as oil, surfactant, and co-surfactant, respectively. The effect of different oil, surfactant and co-surfactant concentrations on particle size, zeta potential and %transmittance was studied using Box–Behnken factorial design. The obtained liquid SMEDDS was evaluated for its thermodynamic stability, globule size, robustness to dilution, viscosity, dye solubilization test, cloud point, etc. Satisfactory formulations of liquid SMEDDS were converted to solid form by adsorption technique using Neusilin US2 as a solid carrier. Evaluation of S-SMEDDS showed that solubility of DG in S-SMEDDS increases from 0.270 to 33.52 mg/mL. In-vitro drug release of S-DG4 showed 99.86 ± 1.47% drug release within 120 minutes while plain DG showed 32.55 ± 1.52%. Hence study revealed that S-SMEDDS is a promising approach to enhance solubility, dissolution and hence bioavailability of poorly aqueous soluble drug like DG.